Competence-building in foreign subsidiaries: The case of new EU member states - Sergey Filippov; Geert Duysters (Journal for East European Management Studies, 2011)
This article examines patterns of competence-building in foreign subsidiaries located in new member states of the European Union. Among the theoretical foundations of this paper are the concepts of dynamic capabilities and subsidiary-specific advantages. We consider subsidiary competences as a combination of distinctive competences built into particular business functions. Furthermore, we examine sources of competences, and complementarities between these sources. We use a proprietary database to examine the research topic and find distinctive uneven growth of functional competences over time, distinctive patterns of complementarities between different functional competences and specific patterns of access to sources of competence. Finally, we discuss managerial and policy implications. – – Dieser Artikel untersucht Muster des Kompetenzaufbaus in ausländischen Niederlassungen, welche in den neuen Mitgliedsstaaten der europäischen Union angesiedelt sind. Das theoretische Fundament dieses Papers bilden die Konzepte der dynamischen Fähigkeiten und niederlassungsspezifischen Vorteile. Wir betrachten das Wissen der Niederlassung als eine Kombination von unterschiedlichen Fähigkeiten die zu speziellen wirtschaftlichen Funktionen kombiniert werden. Des Weiteren untersuchen wir die Quellen von Kompetenzen und Abhängigkeiten zwischen diesen. Wir benutzen eine unternehmenseigene Datenbank um das Forschungsthema zu untersuchen und ausgeprägt unregelmäßiges Wachstum von funktionalen Kompetenzen über die Zeit, markante Muster von Abhängigkeiten zwischen verschiedenen funktionellen Kompetenzen und spezifische Zugangsmodelle zu Kompetenzquellen zu finden. Schließlich diskutieren wir betriebliche und politische Auswirkungen.
Keywords: 650; subsidiaries; multinational; competences; capabilities; subsidiary evolution